Sustainability and strategic development of biogas generated from tofu manufacturing wastewater - Hashfi Hawali Abdul Matin; Sapta Suhardono; Prabang Setyono; Glora Ramadhani; Yoyon Wahyono; Budiyono Budiyono (International Journal of Applied Power Engineering (IJAPE), 2026)
Tofu is a widely consumed soy-based food in Indonesia, and its liquid waste is utilized for biogas in Sambak Village, addressing both renewable energy and waste management issues. However, the system's sustainability faces challenges. This research aimed to assess the current sustainability status of the tofu-wastewater-based biogas system and formulate strategic measures to optimize its long-term continuity. Sustainability was analyzed across five dimensions (ecological, economic, social, technological, and institutional) with multidimensional scaling (MDS) method, while strategies were formulated using SWOT analysis. The results showed an overall moderately sustainable system with an index score of 74.15. The ecological, economic, and social dimensions were rated very sustainable, while the technological dimension was quite sustainable, and the institutional dimension was less sustainable. The top priority strategy identified is the development and innovation of biogas installations. While biogas offers significant environmental and social economic benefits, sustainability is hindered by limited biogas volume and weak institutional management. Therefore, guidance, regular monitoring involving all stakeholders, and future supply-demand forecasting are crucial for its long-term viability.